Growth strategies to fill market sector gap: a case study of DAS Company / Mohd Khairul Nizam Mahmad ... [et al.] - Mahmad, Mohd Khairul Nizam; Rosli, Farah Nor Aishah; Mustaffa, Mohd Taufiq (2015)
The objectives of this research work are to examme internal and external factors for DAS company, to examine the financial performance of the company in addressing current business performance, to determine the state of attractiveness of Malaysian healthy food industry, to identify an appropriate growth strategy for DAS company in healthy food industry and to improving DAS company internal activities by recommend benchmarking as the best practise in the industry. The DAS Company couldn't repeat their sales achievement on 2011. Their selling point focusing more on the new product instead continues with the current product with no proper strategy or any planning without market research and product development. In this study, we used several business tools such as SWOT Analysis, Financial Ratio, Porter'sfive Forces Model, The Strategic Planning Gap and Ansoffs Product Market Growth Matrix and Benchmarking in order to exposed and solve the DAS company problems. From the finding, there are several threat and weakness that should DAS Company overcome and several strength and opportunity that will benefit the company. The financial performance of the company is not too stable. The healthy food industry that they involved was in unattractive industry. Instead of that, there are several market sector gap that they should close. The different strategies needed to promote their products by expanding the size of existing domestic market and enter into the international market through exporting. After year 2012 until current year, their financial ratios are not significant and show negative value. This indicates that the company are putting a risk of not being able to pay back their debts which is a problem because of the company cash flow decline. The DAS Company should stay in the industry even do the healthy food industry in Malaysia is an unattractive industry because the exit barrier is high. The intensive growth comprise of strategies that are been designated to increase either sales or profit over time internally by using the company current business can be apply for the case DAS company. For DAS Company, we are utilizing the 'Best-in-class' benchmarking in light of the fact that we look at their capacities against other association in the same business in their best practice.